2008
DOI: 10.1310/hct0906-418
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Efficacy, and Safety of Darunavir/Ritonavir 800/100 mg Once-Daily in Treatment-Naïve and -Experienced Patients

Abstract: Darunavir is a new protease inhibitor (PI) with in vitro activity against wild-type and PI-resistant HIV; it is used with the pharmacokinetic booster ritonavir. The currently approved dose of darunavir/ritonavir is 600/100 mg twice-daily, licensed for treatment-experienced patients. However, during the clinical development of darunavir, a range of once-daily and twice-daily doses of darunavir/ritonavir were evaluated. The relatively long terminal elimination plasma half-life of darunavir (15 hours) supports on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
49
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 14 publications
6
49
0
5
Order By: Relevance
“…The concentration range of 0.005 to 0.015 M is relatively easily achieved in the clinical use of various PIs. For example, the peak and nadir plasma levels of DRV were ϳ7.1 and 3.4 M when 400 and 100 mg of DRV/RTV were administered twice daily for 7 days (38). Considering that the EC 50 s of GRL-0519 are extremely low, ranging from 0.0005 to 0.030 M (Tables 1 to 4), and that GRL-0519's selectivity index of 63,714 is highly favorable compared to other conventional PIs examined in this study (Table 1), both the anti-HIV potency and safety of GRL-0519 could be favorable, although the efficacy and emergence of adverse effects should be ultimately determined by controlled clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration range of 0.005 to 0.015 M is relatively easily achieved in the clinical use of various PIs. For example, the peak and nadir plasma levels of DRV were ϳ7.1 and 3.4 M when 400 and 100 mg of DRV/RTV were administered twice daily for 7 days (38). Considering that the EC 50 s of GRL-0519 are extremely low, ranging from 0.0005 to 0.030 M (Tables 1 to 4), and that GRL-0519's selectivity index of 63,714 is highly favorable compared to other conventional PIs examined in this study (Table 1), both the anti-HIV potency and safety of GRL-0519 could be favorable, although the efficacy and emergence of adverse effects should be ultimately determined by controlled clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…and DRV/c (800/150 mg q.d.) in HIV-infected patients are broadly similar (53,54). However, in a study conducted in healthy volunteers, it has been reported that the minimum concentration (C min ) of DRV is 30% lower in individuals treated with DRV/c than individuals treated with DRV/r (55).…”
Section: Discussionmentioning
confidence: 92%
“…In subjects taking DRV QD, 52 of 60 (87%) C trough values were above 550 ng/ml, the 50% effective concentration (EC 50 ) (adjusted for protein binding) for resistant virus (7)(8)(9). The lowest measured DRV exposure for the one subject who failed to maintain viral load suppression was 618 ng/ml at week 4.…”
Section: Resultsmentioning
confidence: 99%